2000
DOI: 10.1161/01.cir.102.17.2031
|View full text |Cite
|
Sign up to set email alerts
|

TIMI Risk Score for ST-Elevation Myocardial Infarction: A Convenient, Bedside, Clinical Score for Risk Assessment at Presentation

Abstract: The TIMI risk score for STEMI captures the majority of prognostic information offered by a full logistic regression model but is more readily used at the bedside. This risk assessment tool is likely to be clinically useful in the triage and management of fibrinolytic-eligible patients with STEMI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

23
932
5
62

Year Published

2003
2003
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 1,351 publications
(1,022 citation statements)
references
References 24 publications
23
932
5
62
Order By: Relevance
“…This score was validated in patients with prior myocardial infarction and in patients stabilized after an ACS 16. When applying this score in the IMPROVE‐IT (Improved Reduction of Outcomes: Vytorin Efficacy International Trial) study, high‐risk patients derived the greatest benefit from the addition of ezetimibe to statin therapy 21. This finding is consistent with our findings and emphasize that high‐risk patients may derive the most benefit from guideline‐recommended treatment.…”
Section: Discussionsupporting
confidence: 85%
“…This score was validated in patients with prior myocardial infarction and in patients stabilized after an ACS 16. When applying this score in the IMPROVE‐IT (Improved Reduction of Outcomes: Vytorin Efficacy International Trial) study, high‐risk patients derived the greatest benefit from the addition of ezetimibe to statin therapy 21. This finding is consistent with our findings and emphasize that high‐risk patients may derive the most benefit from guideline‐recommended treatment.…”
Section: Discussionsupporting
confidence: 85%
“…In the past years, several multivariate algorithms have been developed in patients with CP for estimating the need of intensive care [3,[5][6][7]31,32]. However, those studies were performed before troponin testing was routinely available, thus including patients considered at high risk, per se, to date.…”
Section: Discussionmentioning
confidence: 99%
“…In low-risk patients, a stress test aids the evaluation of suspected coronary disease and it is usually performed in the Emergency Department (ED), in the CP unit, or on an outpatient basis shortly after discharge; however, submitting patients to this diagnostic strategy is usually based on unstandardized clinical judgment [2][3][4]. In patients with defined acute coronary syndrome, several prediction rules are available for risk stratification [5][6][7]; conversely, no study has validated the usefulness of a prediction rule including coronary risk factors [8][9][10][11] in a large cohort of patients with low-risk CP. Moreover, some of the major risk factors for atherosclerosis (eg, hypertension, hypercholesterolemia, obesity, cigarette smoking, family history) have been found to be weakly predictive of the likelihood of coronary events in this population [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…Numerous bedside tools have been developed to stratify patients with STEMI to identify a low-risk group of patients who are unlikely to experience complications above the background rate and who can be discharged from the hospital after a brief period of observation. The Zwolle primary PCI index (4) [7] and TIMI-STEMI [8]) and clearly identifies a majority of patients who can be discharged early. Although a more comprehensive score in the setting of primary PCI has since been reported (ie, the Controlled Abciximab and Device Investigation to Lower Late Angioplasty Complications [CADILLAC] [9] score), we found that the Zwolle score was practical as a clinical bedside tool, with the ability to discriminate between high-and low-risk patients.…”
Section: Discussionmentioning
confidence: 99%